Plasma: From Materials to Emerging Technologies - Dors, Mirosław (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Interest in plasma as a tool in various technological processes has been growing for several decades. This is because of the special advantage of plasma, which is the immediate generation of chemically active radicals. There are also other advantages of plasma, which depend on its source, e.g., low or high temperature (dielectric barrier discharge vs. plasmatrons), large or small volume (electron beam chambers vs. microplasma), high or low homogeneity (low pressure RF plasma vs. corona discharge), etc. It is no wonder that plasma is used in so many areas, starting with the synthesis of ozone initiated by Werner von Siemens in 1857, through the activation of material surfaces and flow control by actuators and electrohydrodynamic pumps, to the latest applications related to medicine, environmental protection, and efforts to stop climate change. The objective of this book is to collect reports on the design and characterization of plasma methods which are or can be used in various types of technologies, especially those that solve contemporary problems regarding materials, energy, and the environment.